End detailing experimental study of the pinned double-rectangular tube assembled buckling-restrained brace. (June 2017) - Jiang, Z.Q.; Dou, C.; Guo, Y.L.; Zhang, A.L.
Abstract: Seven pinned double-rectangular tube assembled buckling-restrained brace (DRT-ABRB) specimens are investigated by axial cyclic loading tests in this study. The core member of the specimen is a single flat-plate, with two rectangular tubes assembled to form the external restraining member by high-strength bolts. Each rectangular tube is composed of external channel steel and an external cover plate. The influence of end detailing of DRT-ABRBs on the energy dissipation is explored in the tests, which demonstrates that, compared with the end strengthening measure using an external hoop, the counterpart with a bench ribbed stiffener provides better energy dissipation capacity. In addition, the gap between the bench ribbed stiffener and the external channel steel should be controlled in design. All DRT-ABRBs studied exhibits excellent energy dissipation capacity, which proves the effectiveness of the DRT-ABRB end detailing proposed. Highlights: DRT-ABRB composition and its end detailing are given. Seven pinned DRT-ABRB specimens are investigated by axial cyclic loading tests. The failure mode and energy dissipation capacity of DRT-ABRB are investigated. Appropriate end detailing of this new-type ABRB are proposed. The bench ribbed stiffener detailing of ABRB leads to a fatter hysteretic cycle.